IDENTIFICATION OF GEOCHEMICAL TRACERS WITHIN BIOMINERALS OF JUVENILE AND LARVAL MERCENARIA MERCENARIA : IMPLICATIONS FOR MODELING LARVAL DISPERSAL - Cathey, Andrew M. (East Carolina University, 2013)
This study was designed to investigate the application of geochemical signals within biominerals to identify site fidelity and natal origin of the commercially valuable bivalve Mercenaria mercenaria. My first study investigated the spatiotemporal stability of elemental signals within newly recruited bivalve shell as a means to identify site fidelity within a well-mixed estuarine-lagoonal system. My results demonstrate for the first time the existence of seasonally reproducible small- scale spatial differences (~12-40 km) in the elemental chemistry of juvenile bivalve shell exclusively within an estuarine-lagoonal system. My second study built upon these results and investigated spatiotemporal variability of potential elemental signals within the early larval shell of M. mercenaria as a method to identify natal origin. The results of this investigation demonstrate for the first time the existence of small spatial (~1-50 km) and temporal (tri-weekly) differences in the elemental chemistry of hard clam larval shell. These naturally occurring geochemical tags are indicative of natal origin and may be used trace the dispersal trajectory of this economically important species. My third study empirically investigated the efficacy of the microprobe assay laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) to only target specific areas of interest within M. mercenaria recruited shell. The results of this study suggest that at this time LA-ICP-MS is not a tractable methodology to sample only the retained larval shell of the hard clam without introducing substantial contamination from underlying carbonate.
Keywords: Biological oceanography; Ecology; Carbonate geochemistry; Dispersal; Mercenaria mercenaria; Population ecology; Biology, Ecology; Northern quahog--Larvae--Dispersal; Northern quahog--Larvae--Geographical distribution; Parturition grounds